Perspectives of incretin mimetics in cardiovascular diseases - Cardoso, João Felipe R.; Cohen, Célia; Medeiros, Fernanda J.; Serfaty, Fabiano M.; Neves, Mario F. T. (Brazilian Journal of Health and Biomedical Sciences, 2021)
Introduction: Type 2 Diabetes (DM2) is a chronic condition associated with an increased risk of cardiovascular diseases, neuropathies, nephropathies and eye diseases. Incretins (GIP and GLP-1) are hormones important to insulin secretion, and their actions are compromised in DM2 patients. Objectives: This review considers the opportunities and challenges of using incretin mimetics in the treatment of DM2. Methods: Bibliographic review referring to the period from 2000 to 2020, in electronic databases such as Scielo, Lilacs, PubMed, Web of Science. Results: Incretins stimulate insulin secretion by the pancreas in response to nutrient intake, with a lower potential to cause hypoglycemia. In addition, they have a cardioprotective role, reducing blood pressure, improving endothelial and myocardial function, and their use has been associated with a reduction in the risk of cardiovascular events, including cardiovascular mortality. Clinical trials with GLP-1R agonists (GLP-1RA) reduced albuminuria, increased natriuresis, and decreased oxidative stress. In addition, treatment with incretin mimetics reduced the occurrence of the main cardiovascular outcomes related to atherosclerosis, promoted weight loss and improved lipid profile. Conclusion: Studies show the important role of incretin mimetics in the pathophysiology and treatment of DM2, with significant effects in the cardiovascular system. However, its use must be evaluated in relation to its safety and to in which individuals the benefits outweigh the risks associated with the treatment. Thus, its clinical relevance depends on studies with long-term follow-up of patients, with analysis of its impact on mortality and on the development of micro and macrovascular complications.